Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Kenya - Nyikal, Rose (International Food Policy Research Institute, 2014)
To assess these national capacity needs, the International Food Policy Research Institute (IFPRI) and the Regional Strategic Analysis and Knowledge Support Systems (ReSAKSS) initiated a study in Kenya and other African nations. Twenty-eight Kenyan organizations were determined to be key players in the agricultural policymaking process, but only 11 participated in the study. Overall, the study found that there is a need to build human, financial, and physical capacities for the major stakeholders involved in the Kenyan policymaking process. It also found that a core challenge the agricultural sector faces is the lack of a common platform to share knowledge, tasks, and experiences. A potential solution would be to establish an autonomous body to synchronize communications between stakeholders and assign them definitive tasks that align with their organizational mandates.